Application of appropriate technology for feed supplements in Sukanagalih Village, Tasikmalaya Regency - Andri Kusmayadi; Ghaling Achmad; Yusuf Sumaryana; Ninuk Purnaningsih; Irma Isnafia Arief; Muhamad Syukur; Sulassih Sulassih (University of Merdeka Malang, 2024)
Feed supplement is useful as a growth promoter, increasing efficiency and feed consumption, helping digestion and metabolism, and improving the quality of livestock products. The aim of this community service is to apply appropriate technology to utilize mangosteen peel and turmeric as feed supplement for poultry in Sukanagalih Village, Tasikmalaya Regency, as well as produce quality feed supplement and improve the skills of farmers in processing the supplement feed. This community service activity is one of the Kosabangsa programs between the Universitas Perjuangan Tasikmalaya as the implementation team and the IPB University as the accompanying team. This activity started from September to December 2023 in Sukanagalih Village, Rajapolah District, Tasikmalaya Regency. The method for implementing this activity consists of counseling, training, and assistance to livestock groups. The target partners for this activity were Kelompok Megar Bebek Cihateup and the Berdikari Village-Owned Enterprise (Bumdes Berdikari) with a total of 20 participants each, so the total participants are 40 people. The level of community empowerment increased to 80 – 85% in the knowledge, skills, accessibility, and income categories. The results of this activity are very beneficial for the community, where the application of appropriate technology for processing mangosteen peel and turmeric as feed supplements can increase the added value and selling value of agro-industrial waste products in Tasikmalaya Regency. The application of appropriate technology for the use of supplement feed is able to increase the knowledge and skills of the community in Sukanagalih Village, Tasikmalaya Regency in processing feed supplements.